PENYULUHAN KESEHATAN GIGI DAN MULUT DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN PADA KELAS VIII-1 - Irma Syafriani Br Sinaga; Paska Wira Tigape Sitohang; Berliana Sari (Poltekkes Kemenkes Medan, 2024)
Counseling with Audio Visual Media is a very important means of information because it contains elements of sound and images, which in the process of absorbing material involves the senses of sight and hearing. Lack of knowledge of elementary school age children about oral health is influenced by the lack of information obtained, including in the form of counseling, especially Audio Visual Media. This type of research was descriptive survey method with the aim to find out the description of dental and oral health counseling by using audio-visual media on the knowledge of students of Class VIII-1 at SMP Mulia Pratama Private Medan, with a sample size of 30 people. Data collection was carried out by distributing questionnaires before and after counseling using audio visual media. The results obtained by the data that the level of knowledge of students about oral health before counseling the majority of poor criteria, amounting to 11 people (36.6%). Whereas after counseling, the level of knowledge of students increased to a majority of good criteria, amounting to 27 people (90%), and none of them had bad criteria. The conclusion of this study is an increase in student knowledge about oral health after counseling with audio-visual media and in line with the objectives of counseling. It is expected that schools will provide communication media to increase knowledge, especially dental and oral health for students.